The Development of Scientific Literacy Using Active Learning Management Activities of Seventh-grade Students on Atmosphere and Weather - SEEKEAW, NAPHAT; นาสารีย์ น้ำเพชร; วัจนะ อัมพร (An Online Journal of Education, 2023)
The purposes of this research were (1) to study the scientific literacy of seventh-grade students during their studies and after using active learning management activities for the subjects of atmosphere and weather. (2) to study the satisfaction of seventh-grade students. The target group is 1/3 classroom (6 people) of seventh-grade students from a large-sized school under the Secondary Educational Service Area Office, Bangkok 2. Data were collected during the second semester of the 2022 academic year. The research data collection instruments were (1) active learning lesson plans; (2) a scientific literacy test, and (3) a questionnaire about active learning management. The collected data were analyzed by number, frequency, arithmetic mean, and standard deviation. Overall, the results of the research showed that all students had scientific literacy in a very good level regarding the atmosphere and weather. When considering each lesson plan, it was found that in the 1st and 4th lesson plan on Atmosphere, Clouds, and Rain, all students obtained a very good scientific literacy level. In the 2nd Lesson plan, and 3rd lesson plan on Air Temperature and Humidity, Wind and Air pressure, 83.33% and 66.67% of the students had scientific literacy level in the very good level, respectively. The students were satisfied with the active learning management activities at the highest level (M = 4.75, SD = 0.45).